Efficiency of life insurance companies in Malaysia and Brunei: a comparative analysis - Md Saad, Norma; Haji Idris, Nur Edzalina (Centre for Promoting Ideas, 2011)
This study focuses on the efficiency of the life insurance industry in Brunei and Malaysia. Data Envelopment Analysis(DEA) is used to explore the contributions of technical and efficiency change to the growth of productivity in the Malaysian and Brunei life insurance industries by applying the generalized output-oriented Malmquist index for the year 2000-2005. The output-input data consists of a panel of 9 life insurance firms in Malaysia and 2 life insurance companies in Brunei that were chosen as the sample of the study. This study utilizes two inputs and two outputs, namely, commission and management as well as premium and net investment income, respectively. In the DEA technique, efficiency is measured by the Malmquist index. The Malmquist efficiency measures are decomposed into two components: the efficiency change and technical change index. Efficiency change is again decomposed into pure efficiency and scale efficiency. It is found that, on average, the TFP of the life insurance industry is mainly due to both efficiency and technical changes where the main source of the efficiency change is scale efficiency rather than pure efficiency.